Flavokawain A Reduces Tumor-Initiating Properties and Stemness of Prostate Cancer - Song, Liankun; Mino, Merci; Yamak, Jana; Nguyen, Vyvyan; Lopez, Derron; Pham, Victor; Fazelpour, Ali; Le, Vinh; Fu, Dongjun; Tippin, Matthew; Uchio, Edward; Zi, Xiaolin (Frontiers in Oncology, 2022)
We have previously demonstrated the in vivo chemopreventive efficacy of Flavokawain A (FKA), a novel chalcone from the Kava plant, in prostate carcinogenesis models. However, the mechanisms of FKA’s anti-carcinogenic effects remains largely unknown. We evaluated the effect of FKA on prostate tumor spheroids formation by prostate cancer stem cells, which were sorted out from CD44+/CD133+ prostate cancer cells 22Rv1 and DU145. FKA treatment significantly decreased both size and numbers of the tumor spheroids over different generations of spheroid passages. In addition, dietary feeding of FKA formulated food to NOD/SCID mice bearing CD44+/CD133+ 22Rv1 xenograft tumors resulted in a significant reduction of tumor growth compared to those fed with vehicle control food fed mice. Furthermore, the expression of stem cell markers, such as Nanog, Oct4 and CD44, were markedly downregulated in both tumor spheroids and tumor tissues. We also observed that FKA inhibits Ubc12 neddylation, c-Myc and keratin-8 expression in both CD44+/CD133+ prostate tumor spheroids and xenograft tumors. Our results suggest that FKA can reduce tumor-initiating properties and stemness of prostate cancer, which provides a new mechanism for the chemoprevention efficacy of FKA.